Palgrave advances in peace building critical developments and approaches - Richmond, Oliver P. (Palgrave advances., 2010)
"The quality of the peace arrived at via liberal peace building approaches has been poor. The related state building praxis has generally been unable to respond to its critics. What is at stake is a recognition of peace buildings everyday political, social, economic, and cultural dynamics. This indicates the emergence of a post-liberal form of peace"--Provided by publisher.